A Comparative Analysis of Milk Oligosaccharides via LC-MS : Globally Distributed Cattle Breeds and Native Northern Finncattle - Wang, Yu; Huang, Yu-Ping; Rogers, Mana; Leskinen, Heidi; Soppela, Päivi; Tuomivaara, Anne; Hyvönen, Juha; Barile, Daniela (MDPI, 2024)
Milk oligosaccharides are complex carbohydrates composed of various monosaccharide units linked together by glycosidic bonds. They play an essential role in promoting gut health by fostering beneficial bacteria, supporting the development of the immune system, and protecting against infections and diseases. This work compared the oligosaccharide profiles in widely utilized breeds such as Holstein and Ayrshire (Nordic Red), with the native Northern Finncattle, which is considered an endangered breed. Oligosaccharides were extracted from milk and analyzed by liquid chromatography–mass spectrometry. The composition and relative abundance of the identified oligosaccharides were characterized and compared. The statistical analyses showed that neutral, sialylated, and fucosylated oligosaccharides vary among the breeds. Ayrshire and Northern Finncattle oligosaccharides formed a cluster, while Holstein’s profile shared features with both Ayrshire and Northern Finncattle. Holstein had the lowest abundance of fucosylated OS among the three breeds, with Ayrshire having the highest content followed by Northern Finncattle. The relatively higher sialylated over neutral content of Northern Finncattle is an important feature that should be preserved. Ayrshire is a good candidate to recover more diverse oligosaccharides with potential gut health implications for consumers.
Keywords: dairy; cattle breed; native breed; genetic diversity; milk; oligosaccharides; liquid chromatography-mass spectrometry; LC-MS